Associated factors, triggers and long-term outcome in Complex Regional Pain Syndrome (CRPS) in the upper limb – A descriptive cross-sectional study - Astrid Parinder; Ellen Lyckegård Finn; Lars B. Dahlin; Erika Nyman (PLoS ONE, 2025)
The pathophysiology behind Complex Regional Pain Syndrome (CRPS) is not fully understood and associated factors and triggers for developing the condition are debated. We aimed to study such factors and long-term outcome in a descriptive cross-sectional study with a well-defined population with CRPS in the upper limb and related to sex and CRPS type. In retrospectively collected data from medical records, 149 subjects [women n = 104 (70%); type 1 CRPS, n = 108 (72%); type 2 CRPS, n = 41 (28%); follow-up time 21 [8-43] months] were identified and analysed (Chi-squared test, Mann-Whitney U-test, and multiple linear regression). A majority were manual workers, and a larger proportion of subjects were smokers and had less post-secondary education than a reference population (p < 0.001 and p < 0.008). Men were younger, more frequently smoked, had higher BMI, and had lower education levels than women (p = 0.044, p = 0.007, p < 0.001, and p = 0.016, respectively). Subjects with CRPS type 2 were younger and had a longer time from symptoms until diagnosis, longer follow-up time, and more follow-up visits, indicating worse outcome (p = 0.016, p = 0.0012, p = 0.003, and p = 0.004, respectively). Among CRPS, 32% had a prior pain disorder and 7% had previously visited a pain management clinic. While there was no significant difference in mental illness occurrence before CRPS diagnosis compared to a reference population, mental illness increased by 76% after diagnosis. Factors such as CRPS type 2, older age, and delayed diagnosis were associated with longer follow-up periods. Additionally, 45% were on sick leave for over 12 months, and 20% were permanently unable to work. Socioeconomic deprivation is an associated factor in developing CRPS, in which a variety of triggers exist. Subjects with CRPS, particularly type 2, are at high risk of severe remaining symptoms, including mental illness and risk of never returning to work.